Adaptabilidade e estabilidade fenotípica de progênies F4 de Coffea arabica L. - Dias, Rodrigo Elias Batista Almeida; Carvalho, Gladyston Rodrigues; Botelho, Cesar Elias; de Carvalho, Alex Mendonça [UNESP]; Carvalho, João Paulo Felicori; Cardoso, Diego Abreu (Coffee Science, 2017)
The search for new genotypes with broad stability and adaptability, allied to good agronomic traits has been the main focus of coffee breeding programs in Brazil. With this work, we aimed at selecting C. arabica progenies, related to phenotypic adaptability and stability, to identify the genotypes with best behavior concerning environmental changes. The trial was installed in January of 2007, in the Experimental Fields belonging to EPAMIG, in the municipalities of Machado and São Sebastião do Paraíso, both in Minas Gerais, Brazil. Analyzes of stability and adaptability were done using the methods of Annicchiarico (1992), Ecovalência (WICKE, 1965) and AMMI (ZOBEL, WRIGHT, GAUCH, 1988). The combinations between years and locations were considered as environment for these analyzes. Progeny productivity was evaluated in bags per hectare from 2009 to 2015. In the harvests of 2013, 2014 and 2015, we evaluated agronomic traits related to yield: income determination, yield and sieve analysis. The experimental design used was in randomized blocks, with four replicates and plots constituted of 10 plants. Progenies 107-47-02 Cova 1 and H 105-01-39 Cova 1 presented better behavior concerning environmental variations, allowing the use for generation advancement in the coffee breeding program.
Adaptability and phenotypic stability of F4 progenies of Coffea arabica L.
Keywords: Breeding; Coffee; Environment; Productivity